CCNP ISCW portable command guide - Empson, Scott (Cisco self-study, 2008)
All the CCNP ISCW 642-825 commands in one compact and portable resource All CCNP ISCW commands in an easily referenced resource, no need to be near the Internet for searching online resources Compact size makes it easy to carry with you as a reference in the workplace. No need to carry around big thick books ONLY book published with all CCNP ISCW commands from the only official Cisco certification self study publisher With hundreds of Cisco IOS® Software commands, options, and command arguments to remember, a CCNP ISCW candidate has a lot to commit to memory. Having an easy-to-use, portable reference filled with handy tips and examples on how to apply the commands to real-world scenarios will help increase your familiarity with Cisco IOS Software when working on routers and switches. The CCNP ISCW Portable Command Guide is a supplementary guide to assist network administrators in the proper use of the Cisco IOS and of the commands needed to pass the CCNP ISCW exam. The guide summarizes all ISCW commands, keywords, command arguments, and associated prompts. Configuration examples are provided throughout the book to give a better understanding of how these commands are used in network designs. This guide is not meant to replace any existing learning materials but rather serve as a supplementary guide to assist networkers in the proper use of the many different commands that are required to successfully pass the CCNP ISCW exam. The CCNP ISCW (Implementing Secure Converged WANs) is one of four exams required for the CCNP certification from Cisco, and it focuses on network security and integration technologies.